Risk of cancer in Turkish patients after treatment with TNF antagonists - Pay, S.; Öztürk, M. Akif; Can, Gerçek; Cefle, Ayşe; Çobankara, Veli; Erer, Burak; Yücel, Eftal (Oxford University Press, 2008)
[Abstract Not Available]
Keywords: Adolescent; Adult; Antirheumatic Agents; Arthritis; Female; Humans; Male; Middle Aged; Neoplasms; Risk Assessment; Tumor Necrosis Factor-alpha; adalimumab; etanercept; infliximab; antirheumatic agent; tumor necrosis factor alpha; adult; ankylosing spondylitis; cancer risk; drug substitution; drug withdrawal; female; health survey; hematologic malignancy; human; juvenile rheumatoid arthritis; letter; major clinical study; male; priority journal; psoriatic arthritis; rheumatoid arthritis; risk assessment; risk factor; solid tumor; Turkey (republic); adolescent; arthritis; chemically induced disorder; clinical trial; drug antagonism; middle aged; multicenter study; neoplasm